Association of body mass index with Juvenile Idiopathic Arthritis disease activity - Neto, Agna (2021)
OBJECTIVE: To investigate the relationship between body mass index (BMI) and disease activity in patients with Juvenile Idiopathic Arthritis (JIA). METHODS: Patients with JIA, aged ≤18 years, registered at the Rheumatic Diseases Portuguese Register (Reuma.pt) in Portugal and Brazil were included. Age- and sex-specific BMI percentiles were calculated based on WHO growth standard charts and categorized into underweight (P <3), normal weight (3≤P≤85), overweight (85 <P ≤97) and obesity (P >97). Disease activity was assessed by Juvenile Arthritis Disease Activity Score (JADAS-27). Uni- and multivariate analyses were performed. RESULTS: A total of 275 patients were included. The prevalence of underweight, normal weight, overweight and obesity was 6.9%, 67.3%, 15.3% and 10.5%, respectively. Underweight patients had significantly higher number of active joints (p <0.001), patient's/parent's global assessment of disease activity (PGA) (p=0.020), physician's global assessment of disease activity (PhGA) (p <0.001), erythrocyte sedimentation rate (ESR) (p=0.032) and overall higher JADAS-27 (p <0.001), compared to patients with normal weight, overweight and obesity. In the multivariate regression, underweight persisted significantly associated with higher disease activity, compared to normal weight (B=-9.430, p <0.001), overweight (B=-9.295, p=0.001) and obesity (B=-9.120, p=0.001), when adjusted for age, gender, country, ethnicity, JIA category and therapies used. The diagnosis of RF- (B=3.653, p=0.006) or RF+ polyarticular JIA (B=5.287, p=0.024), the absence of DMARD therapy (B=5.542, p <0.001) and the use of oral GC (B=4.984, p=0.002) were also associated with higher JADAS-27. CONCLUSION: We found an independent association between underweight and higher disease activity in patients with JIA. Further studies are needed to understand the underlying mechanisms of this association.